Sex and Age Comparisons in Neuromuscular And Biomechanical Characteristics of the Knee in Young Athletes - Erin R Pletcher; Travis J Dekker; Scott M Lephart; Tim C Sell (International Journal of Sports Physical Therapy)
# Background The identification of risk factors for injury is a key step for musculoskeletal injury prevention in youth sports. Not identifying and correcting for injury risk factors may result in lost opportunity for athletic development. Physical maturation and sex affect these characteristics, which may indicate the need for both age and sex-based injury prevention programs.